SURFACE RESIDUES: EFFECTS ON SOIL MOISTURE AND TEMPERATURE - Vieira, Gustavo Haddad Souza (2021)
This study aimed to determine how crop residue placement and composition would affect soil water content and temperature during the dry season in the central region of Espírito Santo state, Brazil. A 19-week field study was conducted from April to August 2017. A 2 x 4 factorial study with four replications was implemented using a randomized complete block design. Factors were soil management [conventional tillage (CT) and no soil disturbance (ND)] and residue amendment [maize (Zea mays L.), sunn hemp (Crotalaria juncea L.), a maize-sunn hemp mixture, and a no amendment control]. Soil water content and temperature were measured weekly at predetermined soil depth intervals. Soil water content was higher in ND plots amended with surface residues than under all other treatments in the 0 to 0.05 m depth range. All residue amendments in this range were equally effective in conserving soil water. Surface residues reduced soil temperature by up to 8.4 °C relative to the control in ND plots. Incorporating residue amendments by CT cancelled all temperature-moderating benefits provided by surface residues. These results indicate that surface residues from cereals, legumes, or cereal/legume mixtures are equally effective in conserving soil water and moderating soil temperature during the dry season. Additional research is needed to determine how improved soil environmental conditions, generated by surface residues, would affect nutrient acquisition and crop performance.